2003
DOI: 10.1046/j.1460-9568.2003.02441.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein 4.1B associates with both Caspr/paranodin and Caspr2 at paranodes and juxtaparanodes of myelinated fibres

Abstract: Caspr/paranodin, a neuronal transmembrane glycoprotein, is essential for the structure and function of septate-like paranodal axoglial junctions at nodes of Ranvier. A closely related protein, Caspr2, is concentrated in juxtaparanodal regions where it associates indirectly with the shaker-type potassium channels. Although ultrastructural studies indicate that paranodal complexes are linked to the cytoskeleton, the intracellular partners of Caspr/paranodin, as well as those of Caspr2, are poorly characterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 24 publications
7
120
0
3
Order By: Relevance
“…With its intracellular domain, CASPR2 binds to the 4.1B protein (Denisenko-Nehrbass et al, 2003), which is also known as DAL-1 (Differentially expressed in Adenocarcinoma of the Lung). DAL-1 is a member of the protein 4.1 family and acts as a tumor suppressor in meningiomas (Gutmann et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…With its intracellular domain, CASPR2 binds to the 4.1B protein (Denisenko-Nehrbass et al, 2003), which is also known as DAL-1 (Differentially expressed in Adenocarcinoma of the Lung). DAL-1 is a member of the protein 4.1 family and acts as a tumor suppressor in meningiomas (Gutmann et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the juxtaparanodal region, Kv1.1 and Kv1.2 have been shown to colocalize with, and to interact and͞or cluster with, Caspr2, a member of the neurexin superfamily (49,50). Indeed Caspr2 also interacts with other proteins necessary for the accumulation of Kv channels at the juxtaparanodal region and for their interaction with the actin-spectrin cytoskeleton (14, [51][52][53][54][55][56]. The present results show that in human neocortical pyramidal cells, Kv1.2 channels are clustered at and colocalize with the adhesion molecule Caspr2 exclusively in the distal domain of the AIS.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoskeletal disorganization observed in the NCP1 and CGT mutants suggest that the molecular link between AGJs and the axonal cytoskeleton is important for local arrangement of the cytoskeletal network in Purkinje axons. Other proteins identified as part of the paranodal complex include CNTN and a brain-specific isoform of actin͞spectrin-binding protein, band 4.1B (27). We therefore carried out immunoprecipitation experiments using anti-NCP1 antibodies on membrane-enriched cerebellar lysates from WT and NCP1 and CGT mutants.…”
Section: Axonal Swellings Display Organelle Accumulation and Cytoskelmentioning
confidence: 99%
“…NCP1 is the only identified AGJ axonal protein that contains a cytoplasmic domain. Evidence gathered from biochemical and transgenic mice studies showed that the cytoplasmic domain of NCP1 binds to the actin-spectrin binding protein 4.1B (27,28). There is growing realization that NCP1 mediates AGJ interactions with the axonal cytoskeleton and may participate in axon-glial signaling; however, physiological evidence to support these assumptions remains to be established.…”
mentioning
confidence: 99%